"Shades of Gray" in pancreatic ductal adenocarcinoma: Reappraisals on resectability criteria: Debated indications for surgery in pancreatic cancer. (January 2019) - Lombardi, P.; Silvestri, S.; Marino, D.; Santarelli, M.; Campra, D.; De Paolis, P.; Aglietta, M.; Leone, F.; ,
Abstract: Pancreatic ductal adenocarcinoma is one of the leading causes of cancer-related deaths and, currently, surgery is the only curative treatment. Patients with borderline resectable pancreatic cancer (BRPC) can benefit from a multidisciplinary approach and R0 resection, and can achieve the same outcome as resectable patients treated with upfront surgery. However, the definition of BRPC changes according to different classifications with a heterogeneous distribution of patients, and it is thus difficult to compare clinical evidence. We performed a literature review to assess the most suitable classification of BRPC. Our review was conducted using the PubMed database. Only articles containing more than ten patients classified according to NCCN, MDACC or AHPBA/SSAT/SSO classifications were selected. A total of 16 studies were included in our analysis, and were grouped according to one of these three classifications. The total resection rate was 61.4%, with considerable differences between the groups (68.4% for NCCN, 54.9% for MDACC and 53.2% for AHPBA/SSO/SSAT). The total R0 resection rate was 90.1% (89.1% for NCCN, 92.5% for MDACC and 84% for AHPBA/SSO/SSAT). Of the three classifications, NCCN limits the use of confusing terms and uses restrictive criteria to define the most appropriate treatment for each subgroup. However, several reports have suggested that, even in the case of a limited disease, biological and clinical factors should be considered in order to classify patients as resectable. NCCN classification appears to be the classification that allows the highest percentage of patients with BRPC to achieve resection without reducing the R0 resection rate. The choice of therapy should not only be based on imaging results, but also on a wider clinical multidisciplinary evaluation.